Appropriate technology for processing of plantation products for the mekar association of the bugis transmigrant tribe in Pal Village IX - Rochmawati, Rochmawati; Waspodo, Waspodo; Fachri, Helman; Selviana, Selviana; Suwarni, Linda (Universitas Muhammadiyah Magelang, 2021)
Pal IX village has a potential plantation, namely banana. The products of this plantation are utilized by the Mekar Women's Association (Parwa), which consists of transmigrant women from the Bugis tribe who process bananas into dodol, chips, and kapok bread. The problem faced is that the processing of products is still manual (traditional), so that the products produced are limited. In addition, product marketing still relies on existing orders and has not paid attention to the food sanitation hygiene produced. The introduction of appropriate technology is needed to overcome this problem. Implementation of activities using the method of education and mentoring and carried out for 4 months. The results of the activity showed an increase in the group's knowledge and skills in applying appropriate technology, and changes in online-based marketing strategies.